Analisis Berpikir Literasi Matematika Berdasarkan Kecerdasan Logika Matematika Siswa SMP - Maria Ulfah; Hamidah Suryani Lukman; Novi Andri Nurcahyono (ARITHMETIC: Academic Journal of Math, 2020)
Based on preliminary analysis, students’ mathematics literacy thinking skills are relatively low. One of the factors that affected it is mathematics logic intelligence. This research aims to describe the students mathematics literacy thinking skills based on high, medium and low intelligence mathematics logic. This research is a inquiry study with a qualitative approach and descriptive qualitative research design and data collection techniques in the form of questionnaries and tests. The subjects in this study were three students of 8th grades of SMP Negeri 1 Sukabumi city, the type of subject taking in this study using the purposive sampling. Based on the results of the study, the students that possesses a high mathematics logic intelligence reach the three components of mathematics literacy thinking that formulate mathematical situations, applying mathematics concepts, facts, procedures, and mathematics reasoning, and interpret, applying and evaluate the results. Students who acquire mathematics logic intelligence categories are fulfilling the two components of mathematics literacy thinking namely formulating mathematical situations and applying mathematics concepts, facts, procedures and mathematics reasoning. Meanwhile, the students that possesses a low mathematics logic intelligence reach one indicator of one component of mathematics literacy thinking ability.